2022
DOI: 10.3390/ijerph19031324
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Prolonged Inferior Alveolar Nerve Blockade for Postoperative Analgesia in Mandibular Third Molar Surgery by a Perineural Addition of Dexamethasone to 0.5% Ropivacaine: A Randomized Comparison Study

Abstract: Background: Perineurally adding dexamethasone to local anesthetics could enable postoperative analgesia. Our aim was to investigate the efficacy of 4 mg dexamethasone and 0.5% ropivacaine on the prolonged duration of mandibular anesthesia for postoperative analgesia during third molar surgery. Materials and method: The patients of both sexes, and in the age range of 17 to 50 yrs of age, received the Gow-Gates anesthesia. Group I received 4 mL of plain 0.5% ropivacaine, with perineurally added 1 mL/4 mg of dexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 77 publications
(96 reference statements)
1
8
0
2
Order By: Relevance
“…The success rate of IANB was 96.1% in the current study. According to previous studies, IANB had a success rates ranging from 71.5% to 100% 1,5,13,17–21,25,26 . It has been shown that intern trainers achieve a 97.6% success rate.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The success rate of IANB was 96.1% in the current study. According to previous studies, IANB had a success rates ranging from 71.5% to 100% 1,5,13,17–21,25,26 . It has been shown that intern trainers achieve a 97.6% success rate.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies found that positive aspirations of IANB ranged from 0% to 46.4% 9,12–20 . Several factors may explain this wide range, including the skills of the operator, the types of dental syringes and the gauge of the needle used in different studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, a variety of injection methods have been described in the literature, all of which intended to improve the success rate of IAN block and avoid complications, although all have advantages and disadvantages (8,9). Gow-Gates mandibular nerve conduction anesthesia is reported to have a success rate up to 93% in a recent report (10). But this method has a long onset and a vague injection site location that is difficult to determine (7,11).…”
Section: Introductionmentioning
confidence: 99%